1998
DOI: 10.1016/s0008-6363(98)00188-6
|View full text |Cite
|
Sign up to set email alerts
|

An inhibitor of nitric oxide synthase does not increase contraction or β-adrenoceptor sensitivity of ventricular myocytes from failing human heart

Abstract: These results do not suggest a functional role for tonic NO production in the frequency-dependent depression of contraction or beta-adrenoceptor desensitisation in myocytes from failing human ventricle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…That is, when there was no effect of NOS2 inhibition on the ISO response, a large response to ␤-AR stimulation was already seen in the trabeculae and isolated cardiac myocytes (failing and nonfailing human hearts). In the minority of HF cases in which NOS2 is not expressed, the ISO response was similar to what we observed in trabeculae and myocytes isolated from nonfailing human heart ( Figures 3 and 4 and similar to previous studies in nonfailing trabeculae and myocytes 15,18,23 ). Thus, we conclude that NOS2 expression is a key element in the ␤-AR hyporesponsiveness associated with human HF.…”
Section: Responsiveness In Human Hfsupporting
confidence: 90%
See 1 more Smart Citation
“…That is, when there was no effect of NOS2 inhibition on the ISO response, a large response to ␤-AR stimulation was already seen in the trabeculae and isolated cardiac myocytes (failing and nonfailing human hearts). In the minority of HF cases in which NOS2 is not expressed, the ISO response was similar to what we observed in trabeculae and myocytes isolated from nonfailing human heart ( Figures 3 and 4 and similar to previous studies in nonfailing trabeculae and myocytes 15,18,23 ). Thus, we conclude that NOS2 expression is a key element in the ␤-AR hyporesponsiveness associated with human HF.…”
Section: Responsiveness In Human Hfsupporting
confidence: 90%
“…22 In addition, it has been found that nonspecific NOS inhibition had no effect on the ISO response in myocytes isolated from failing human hearts. 23 We show here that specific NOS2 inhibition greatly enhanced the response to ␤-AR stimulation in trabeculae from failing human hearts (Figure 1). We also show that specific NOS2 inhibition in isolated cardiac myocytes from failing human hearts restored the ␤-AR response (Figure 2).…”
Section: Effects Of Nos2 Inhibition On ␤-Ar Response In Human Hfmentioning
confidence: 67%
“…These data are consistent with the lack of effect of NOS inhibition on the response of isolated failing human cardiomyocytes to pacing. 31 …”
Section: No and The Myocardial Ffr In The Human Heartmentioning
confidence: 99%
“…Unlike the ␤-adrenergic response, the positive forcefrequency relationship that is blunted in CHF patients is also insensitive to NOS inhibitors, 35 as is the shortening amplitude of isolated cardiomyocytes from HF patients when increasing pacing rate from 0.2 to 1 Hz. 112 Clearly, additional patho- …”
mentioning
confidence: 99%